Household composition and child health in Botswana - Oleosi Ntshebe; Andrew Amos Channon; Victoria Hosegood (BMC, 2019)
Abstract Background There is a general lack of research on children's household experiences and child health outcomes in low- and middle-income countries (LMICs). This study examines the relationship between household composition, stunting and diarrhoea prevalence among children younger than 5 years of age in Botswana. Methods The analysis uses data from the 2007 Botswana Family Health Survey (BFHS) and multilevel logistic regression models. Results The findings indicate that stunting varies by whom the child lives with. Stunting is higher among children living with no parents compared to those living with both parents. Stunting is also high among children living with unrelated household members. Similarly, children in households with a mother-only and with a grandparent present, have a higher level of stunting compared to those living with both parents. Conversely, living with an aunt and living with other relatives, protects against stunting. The findings on diarrhoea prevalence show that children living in mother-only households and those living with no parents are less likely to have diarrhoea than those living with both parents. Also, across all households, those who are more affluent have lower rates of child stunting and diarrhoea than those which are more deprived. Finally, the findings show a clustering effect at the household level for both stunting and diarrhoea prevalence. Conclusions These findings suggest that policies and programs aimed at reducing stunting and diarrhoea may work best if they target households and other adults co-residing in homes with children besides biological parents. Further, children who live in poorer households deserve special attention.